Membongkar Paradigma Positivisme Hukum dalam Pemberantasan Korupsi di Indonesia: Pemenuhan Hak Asasi Manusia dalam Negara Hukum - Habib Shulton Asnawi (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2013)
Thinking in this paper, motivated by concerns about increasing corruption cases in Indonesia, both central to the regional level. This is due to law enforcement (Judges, Prosecutors and Police) in Indonesia is still dominated by the paradigm and way of thinking "positivistic-legalistic", especially in the interpretation of law. Corruption affects the country's financial losses, destroying human resource, social, natural, democratic system and the rule of law. Thus resulting in poverty, ignorance, misery, and destruction of the Indonesian nation. Therefore, dismantle legal positivism paradigm is a necessity, in order to fulfill Human Rights (HAM) notably in the concept of rule of law in Indonesia.